The 2004 Aceh‐Andaman Earthquake: Early clay dehydration controls shallow seismic rupture. (3rd September 2013) - Geersen, Jacob; McNeill, Lisa; Henstock, Timothy J.; Gaedicke, Christoph
<x xml:space="preserve">Abstract</x> [1] The physical state of the shallow plate‐boundary fault governs the updip extent of seismic rupture during powerful subduction zone earthquakes and thus on a first order impacts on the tsunamigenic hazard of such events. During the 2004 Mw 9.2 Aceh‐Andaman Earthquake seismic rupture extended unusually far seaward below the accretionary prism causing the disastrous Indian Ocean Tsunami. Here we show that the formation of a strong bulk sediment section and a high fluid‐pressured predécollement, that likely enabled the 2004 rupture to reach the shallow plate‐boundary, result from thermally controlled diagenetic processes in the upper oceanic basement and overlying sediments. Thickening of the sediment section to >2 km ∼160 km seaward of the subduction zone increases temperatures at the sediment basement interface and triggers mineral transformation and dehydration (e.g., smectite‐illite) prior to subduction. The liberated fluids migrate into a layer that likely host high porosity and permeability and that is unique to the 2004 rupture area where they generate a distinct overpressured predécollement. Clay mineral transformation further supports processes of semilithification, induration of sediments, and coupled with compaction dewatering all amplified by the thick sediment section together strengthens the bulk sediments. Farther south, where the 2005 Sumatra Earthquake did not include similar shallow rupture, sediment thickness on the oceanic plate is significantly smaller. Therefore, similar diagenetic processes occur later and deeper in the subduction zone. Hence, we propose that shallow seismic rupture during the 2004 earthquake is primarily controlled by the thickness and composition of oceanic plate sediments.